Empty Box Legality as A Form of Democratic Betrayal - Faisal, Thomy (Green Publisher Indonesia, 2024)
The legality of empty boxes in Indonesia's elections raises critical questions about democratic legitimacy and public trust. Empty boxes often symbolize voter dissatisfaction with candidates, reflecting deeper systemic issues within the democratic framework. This study examines the legality and implications of empty boxes, employing a normative juridical approach to analyze legal and political perspectives. Data were collected through a legislative, comparative, and case-based approach, followed by descriptive analysis. The findings reveal that while empty boxes can serve as a form of protest, they also highlight the limitations of political parties in presenting viable candidates. This phenomenon undermines the legitimacy of electoral outcomes and public trust in democratic institutions. By exploring voter behavior, legal frameworks, and historical precedents, this research identifies the empty box phenomenon as a critical challenge to Indonesia's democracy. The study concludes that addressing the root causes of voter dissatisfaction and promoting political competition are essential for safeguarding democratic integrity. This research contributes to the discourse on electoral governance and offers recommendations for strengthening Indonesia's democratic processes.